2017
DOI: 10.1111/1911-3846.12342
|View full text |Cite
|
Sign up to set email alerts
|

The Worth of Fair Value Accounting: Dissonance between Users and Standard Setters

Abstract: Investors and analysts are designated as the primary users of financial reports by standard setters, yet we know very little about their use of accounting information and about their relationship with standard setters. This paper explores how investors and analysts evaluate the usefulness of fair values to their work. Standard setters typically presume that investors and analysts view accounting as a practice of valuation and, therefore, favor the greater use of fair value measurement. However, using interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 122 publications
0
77
0
Order By: Relevance
“…see Whittington, 2016), it is made explicit in the IASB's new CF: 'The Board concluded that in different circumstances different measurement bases may provide information relevant to users of financial statements' (CF2018.BC6.10). Such an acknowledgment resonates with the opinions of constituents (CF2018.BC6.7) and also with empirical research on users' assessments of measurement bases (Gassen & Schwedler, 2010;Georgiou, 2018). In such a setting, where the standard-setter does not favor one particular measurement basis per se, the consideration of QCs becomes an important issue.…”
Section: Discussionmentioning
confidence: 78%
“…see Whittington, 2016), it is made explicit in the IASB's new CF: 'The Board concluded that in different circumstances different measurement bases may provide information relevant to users of financial statements' (CF2018.BC6.10). Such an acknowledgment resonates with the opinions of constituents (CF2018.BC6.7) and also with empirical research on users' assessments of measurement bases (Gassen & Schwedler, 2010;Georgiou, 2018). In such a setting, where the standard-setter does not favor one particular measurement basis per se, the consideration of QCs becomes an important issue.…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, we did not adopt a linear process to our analysis but rather moved back and forth between data and theory in an abductive fashion to gain better insights to our research questions (Ahrens and Chapman ). Case quotations and observational details are used throughout the discussion as illustrative examples of the empirical findings and as a means of enabling readers to “hear” voices from the field (Georgiou ). Examples were chosen for one of two reasons.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, many accounting research departments and standard setters demonstrate support for fair value accounting. Therefore, there is an actual possibility that accounting systems will move further in the direction of fair value accounting (Cardao-Pito and Ferreira, 2018b; Georgiou, 2018; Mora et al., 2019; Rayman, 2007).…”
Section: Fair Value Accounting Must Be Considered With Its Three Levelsmentioning
confidence: 99%